The experiences of teachers of mathematics in classroom work with blind people - Bolaños-González, Helen (2016)
This article aims to present the point of view of professors of mathematics about the comprehensive care for the blind or low-vision population. It is important to collect the experiences that Mathematics teachers of the National University of Costa Rica have had with students with visual disabilities, and thus to have a history of what has been done, and the results obtained when applying some methodological strategies. This paper seeks to represent the teachers’ opinion on the challenges they must face to carry out the methodological approach and the evaluation process of teaching Mathematics. The development of the research was based on a case study of a blind student who repeatedly failed the course of Differential and Integral Calculus, and therefore interviewing the staff responsible for giving him attention during the second semester 2014 was considered. Based on the above, the information provided by the teachers and the staff responsible for providing supervision and support to students with visual disabilities was analyzed. Such information represents the experiences of students in courses of Mathematics and the main characteristics of their learning. Among the most important results of this work are the features of the methodology and the process of evaluation used in a Mathematics class for blind students, as well as the major needs visually-impaired students have in this discipline, in order to improve the favorable conditions that the School of Mathematics of the National University of Costa Rica has been creating in relation with inclusive education